A composite hydrogel material, a preparation method and application thereof, and a hydrogen adsorption-storage-release system and method
Patent Information
- Application Number
- CN202611065176.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-08-18
AI Technical Summary
然而,氢气原位富集技术目前主要面向高浓度氢气气源,对低浓度氢气储层的适应性严重不足,主要原因如下:活性炭、沸石等常规吸附剂对氢气储层中H2/CH4的选择性普遍低于50,难以从地层混合气中高效分离氢气;吸附后氢气的释放需要采用热脱附法,需整体加热储层,能耗高且释放速率不可控;枯竭油气藏中含有的H2S气体会腐蚀吸附材料,导致材料寿命短,微生物滋生进一步加剧系统失稳
[0014]This invention provides a composite hydrogel material, comprising a composite gel core and a silicon carbide layer coating the surface of the composite gel core; the composite gel core is a polyacrylamide-based hydrogel and a thermosensitive copolymer grafted onto the polyacrylamide-based hydrogel; the polyacrylamide-based hydrogel and the thermosensitive copolymer form an interpenetrating network or a semi-interpenetrating network; MOF-808(Zr) nanoparticles are dispersed in the polyacrylamide-based hydrogel; the pore size of the MOF-808(Zr) nanoparticles is 0.29~0.3 nm; gold nanorods are dispersed in the thermosensitive copolymer; the local surface plasmon resonance peak value of the gold nanorods is 798~818 nm. The composite hydrogel material provided by this invention achieves selective adsorption of hydrogen through MOF-808(Zr) nanoparticles with a pore size of 0.29~0.3 nm. H2 with a molecular diameter of 0.289 nm can enter the channels of MOF-808(Zr) nanoparticles and be selectively adsorbed, while CH4 with a molecular diameter of 0.38 nm is blocked by the kinetic quantum sieving effect, achieving highly selective adsorption of H2. The H2/CH4 selectivity is >500 at 298 K and 1 bar pressure, and the hydrogen adsorption capacity reaches more than 1.2 wt% at a low pressure of 0.1 bar. After adsorption saturation, the hydrophobic groups of the thermosensitive polymer in the composite hydrogel material trigger hydrophobic shrinkage, resulting in a hydrogen diffusion coefficient ≤5×10⁻⁶. -13 m 2 The closed hydrogen storage unit, with a capacity of /s, enables H2 storage. Polyacrylamide-based hydrogels and thermosensitive copolymers form an interpenetrating or semi-interpenetrating network, collectively constituting the composite gel core of the composite hydrogel material. Gold nanorods are dispersed in the thermosensitive copolymer, with a local surface plasmon resonance peak of 798-818 nm. Under near-infrared light irradiation in the corresponding wavelength band, it can achieve a photothermal conversion efficiency exceeding 85%, triggering a local temperature rise to above 50°C within 5 seconds, causing the thermosensitive copolymer to dissolve and inducing a volume phase transition and shrinkage of the composite gel core, achieving controlled H2 release. A silicon carbide layer serves as the outer shell, possessing anti-corrosion and catalytic oxidation anti-poisoning mechanisms, extending the lifespan of the composite hydrogel material in sulfur-containing formations by 5 times and exhibiting strong resistance to hydrogen sulfide corrosion. Furthermore, the composite hydrogel material provided by this invention is simple to use; by preparing a solution containing hydrogen adsorbent, it can be directly injected into the reservoir, fully compatible with existing wellbore facilities. Controlled hydrogen release can be achieved under near-infrared light irradiation without thermal desorption, reducing the cost of hydrogen enrichment and recovery.
Smart Images

Figure CN122582924A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen separation and recovery technology, specifically to a composite hydrogel material and its preparation method and application, and a system and method for hydrogen adsorption-storage-release. Background Technology
[0002] Hydrogen, as a clean energy carrier, holds significant strategic importance for in-situ enrichment and recovery in depleted oil and gas reservoirs. However, current in-situ hydrogen enrichment technologies primarily target high-concentration hydrogen sources, exhibiting severely limited adaptability to low-concentration hydrogen reservoirs. The main reasons are as follows: conventional adsorbents such as activated carbon and zeolite generally have an H2 / CH4 selectivity of less than 50 in hydrogen reservoirs, making it difficult to efficiently separate hydrogen from the formation mixture; the release of adsorbed hydrogen requires thermal desorption, necessitating overall reservoir heating, resulting in high energy consumption and uncontrollable release rates; and the H2S gas present in depleted oil and gas reservoirs corrodes adsorbent materials, leading to short material lifespans and further exacerbating system instability due to microbial growth. Therefore, there is an urgent need for an adsorbent material that integrates highly selective hydrogen adsorption, precise triggering of release, and long-term resistance to hydrogen sulfide corrosion to achieve in-situ enrichment and controllable recovery of hydrogen in depleted oil and gas reservoirs. Summary of the Invention
[0003] In view of this, the purpose of this invention is to provide a composite hydrogel material, its preparation method and application, and a system and method for hydrogen adsorption-storage-release. The composite hydrogel material provided by this invention can achieve highly selective adsorption, storage and controlled release of hydrogen, and has strong resistance to hydrogen sulfide corrosion.
[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a composite hydrogel material, comprising a composite gel core and a silicon carbide layer coating the surface of the composite gel core; The composite gel core consists of a polyacrylamide-based hydrogel and a thermosensitive copolymer grafted onto the polyacrylamide-based hydrogel; the polyacrylamide-based hydrogel and the thermosensitive copolymer form an interpenetrating network or a semi-interpenetrating network; MOF-808(Zr) nanoparticles are dispersed in the polyacrylamide-based hydrogel; the pore size of the MOF-808(Zr) nanoparticles is 0.29~0.3 nm; The thermosensitive copolymer contains gold nanorods; the local surface plasmon resonance peak of the gold nanorods is 798~818 nm.
[0005] Preferably, the particle size of the MOF-808(Zr) nanoparticles is 50~200nm; the mass ratio of the MOF-808(Zr) nanoparticles to the polyacrylamide-based hydrogel is 1~3:10.
[0006] Preferably, the mass ratio of the polyacrylamide-based hydrogel to the thermosensitive copolymer is 1:0.5~2; The critical dissolution temperature of the thermosensitive copolymer is 43~47℃; The polymer monomers of the thermosensitive copolymer include a first acrylamide monomer and an acrylic monomer; The first acrylamide monomer includes one or more of N-isopropylacrylamide, N,N-diethylacrylamide and N-tert-butylacrylamide; The acrylic monomers include one or more of acrylic acid, methacrylic acid, ethylacrylic acid, butenoic acid, and 2-ethylacrylic acid; The molar ratio of the first acrylamide monomer to the acrylic monomer is 6.7~9:1; The ratio of the total volume of the polyacrylamide-based hydrogel and the thermosensitive copolymer to the mass of the gold nanorods is 1 mL: 0.5~2 mg; The aspect ratio of the gold nanorods is 3~5:1.
[0007] Preferably, the polyacrylamide-based hydrogel also contains a palladium catalyst; The palladium catalyst comprises cerium dioxide and elemental palladium supported on the cerium dioxide.
[0008] This invention provides a method for preparing the composite hydrogel material described above, comprising the following steps: The second acrylamide monomer, crosslinking agent, initiator, MOF-808 (Zr) nanoparticles and water were mixed to obtain a mixed dispersion. The mixed dispersion is subjected to a crosslinking reaction in the oil phase, or the mixed dispersion is subjected to a crosslinking reaction in a spherical mold to obtain a spherical primary hydrogel; The spherical primary hydrogel, the polymer monomer of the thermosensitive copolymer, gold nanorods, and a polar aprotic solvent were mixed and subjected to a polymerization-grafting reaction to obtain a composite gel core. A silicon carbide layer is formed on the surface of the composite gel core to obtain a composite hydrogel material.
[0009] Preferably, the crosslinking agent includes one or more of N,N'-methylenebisacrylamide, p-divinylbenzene, N,N'-bis(acryloyl)cysteine, tetraallylpropoxyethane, ethylene glycol diacrylate and diacetone acrylamide; The initiator includes one or more of azo initiators, peroxide initiators, persulfate initiators, photoinitiators, and redox initiators; The mass ratio of the second acrylamide monomer to the crosslinking agent is 100:0.5~3; The mass ratio of the second acrylamide monomer to the initiator is 100:0.5~1.5; The crosslinking reaction was carried out at a temperature of 60°C for 2 hours. The polymerization-grafting reaction is carried out at a temperature of 25°C for 1 to 4 hours.
[0010] Preferably, when the composite gel core also contains a palladium catalyst, the preparation method of the composite hydrogel material includes the following steps: The second acrylamide monomer, crosslinking agent, initiator, MOF-808 (Zr) nanoparticles, palladium catalyst and water were mixed to obtain a mixed dispersion. The mixed dispersion is subjected to a crosslinking reaction in the oil phase, or the mixed dispersion is subjected to a crosslinking reaction in a spherical mold to obtain a spherical primary hydrogel; The spherical primary hydrogel, the polymer monomer of the thermosensitive copolymer, gold nanorods, and a polar aprotic solvent were mixed and subjected to a polymerization-grafting reaction to obtain a composite gel core. A silicon carbide layer is formed on the surface of the composite gel core to obtain a composite hydrogel material.
[0011] This invention provides the application of the composite hydrogel material described in the above technical solution or the composite hydrogel material prepared by the above technical solution in the adsorption, storage and controlled release of hydrogen.
[0012] This invention provides a hydrogen adsorption-storage-release system, comprising a hydrogen adsorption material and a near-infrared light source; The hydrogen adsorption material is the composite hydrogel material described in the above technical solution or the composite hydrogel material prepared by the preparation method described in the above technical solution.
[0013] This invention provides a method for hydrogen adsorption-storage-release using the system described above, wherein the adsorption and storage include: injecting a solution containing hydrogen adsorption material into an aqueous hydrogen storage layer, so that the hydrogen adsorption material adsorbs hydrogen in the aqueous hydrogen storage layer to obtain a closed hydrogen storage unit. The release includes: irradiating the sealed hydrogen storage unit with a near-infrared light source to cause the sealed hydrogen storage unit to release hydrogen gas.
[0014] This invention provides a composite hydrogel material, comprising a composite gel core and a silicon carbide layer coating the surface of the composite gel core; the composite gel core is a polyacrylamide-based hydrogel and a thermosensitive copolymer grafted onto the polyacrylamide-based hydrogel; the polyacrylamide-based hydrogel and the thermosensitive copolymer form an interpenetrating network or a semi-interpenetrating network; MOF-808(Zr) nanoparticles are dispersed in the polyacrylamide-based hydrogel; the pore size of the MOF-808(Zr) nanoparticles is 0.29~0.3 nm; gold nanorods are dispersed in the thermosensitive copolymer; the local surface plasmon resonance peak value of the gold nanorods is 798~818 nm. The composite hydrogel material provided by this invention achieves selective adsorption of hydrogen through MOF-808(Zr) nanoparticles with a pore size of 0.29~0.3 nm. H2 with a molecular diameter of 0.289 nm can enter the channels of MOF-808(Zr) nanoparticles and be selectively adsorbed, while CH4 with a molecular diameter of 0.38 nm is blocked by the kinetic quantum sieving effect, achieving highly selective adsorption of H2. The H2 / CH4 selectivity is >500 at 298 K and 1 bar pressure, and the hydrogen adsorption capacity reaches more than 1.2 wt% at a low pressure of 0.1 bar. After adsorption saturation, the hydrophobic groups of the thermosensitive polymer in the composite hydrogel material trigger hydrophobic shrinkage, resulting in a hydrogen diffusion coefficient ≤5×10⁻⁶. -13 m 2 The closed hydrogen storage unit, with a capacity of / s, enables H2 storage. Polyacrylamide-based hydrogels and thermosensitive copolymers form an interpenetrating or semi-interpenetrating network, collectively constituting the composite gel core of the composite hydrogel material. Gold nanorods are dispersed in the thermosensitive copolymer, with a local surface plasmon resonance peak of 798-818 nm. Under near-infrared light irradiation in the corresponding wavelength band, it can achieve a photothermal conversion efficiency exceeding 85%, triggering a local temperature rise to above 50°C within 5 seconds, causing the thermosensitive copolymer to dissolve and inducing a volume phase transition and shrinkage of the composite gel core, achieving controlled H2 release. A silicon carbide layer serves as the outer shell, possessing anti-corrosion and catalytic oxidation anti-poisoning mechanisms, extending the lifespan of the composite hydrogel material in sulfur-containing formations by 5 times and exhibiting strong resistance to hydrogen sulfide corrosion. Furthermore, the composite hydrogel material provided by this invention is simple to use; by preparing a solution containing hydrogen adsorbent, it can be directly injected into the reservoir, fully compatible with existing wellbore facilities. Controlled hydrogen release can be achieved under near-infrared light irradiation without thermal desorption, reducing the cost of hydrogen enrichment and recovery. Attached Figure Description
[0015] Figure 1 A schematic diagram of the structure of the composite hydrogel material provided by the present invention; Figure 2 The present invention provides a flowchart of a hydrogen adsorption-storage-release method; Figure 3 The present invention provides a flowchart of a hydrogen adsorption-storage-release method; Figure 3 A schematic diagram of the in-situ adsorption and permeation diffusion mechanism of hydrogen in underground reservoirs; Figure 4 A schematic diagram illustrating the adsorption and storage principle of composite hydrogel materials; Figure 5 A schematic diagram of the kinetic quantum sieving effect process of MOF-808(Zr) nanoparticles; Figure 6 A schematic diagram illustrating the principle of releasing hydrogen from a closed hydrogen storage unit; Figure 7 This is a schematic diagram illustrating the corrosion resistance principle of composite hydrogel materials. Figure 1 and Figures 3-7 In the diagram, 1-polyacrylamide-based hydrogel, 2-thermosensitive copolymer, 3-silicon carbide layer, 4-MOF-808(Zr), 5-gold nanorods, 6-palladium catalyst, 7-injection well, 8-production well, 9-swollen microspheres, 10-H2 molecule, 11-hydrogen migration and diffusion concentration, 12-solution permeation and diffusion concentration of hydrogen-containing adsorbent material, 13-formation water, 14-CH4 molecule, 15-porous structure of swollen microspheres, 16-hydrophobic group, 17-hydrogel shrinkage region, 18-H2S molecule, 19-MOF-808(Zr) channel, 20-MOF-808(Zr) pore size, 21-H2 molecule diameter, 22-CH4 molecule diameter, 23-near-infrared light source, 24-thermal radiation, 25-volume phase transition shrinkage region, 26-elemental S; 27-reaction product water molecule; 28-catalytic oxidation and corrosion-resistant region, 29-underground reservoir. Detailed Implementation
[0016] This invention provides a composite hydrogel material, comprising a composite gel core and a silicon carbide layer coating the surface of the composite gel core; The composite gel core consists of a polyacrylamide-based hydrogel and a thermosensitive copolymer grafted onto the polyacrylamide-based hydrogel; the polyacrylamide-based hydrogel and the thermosensitive copolymer form an interpenetrating network or a semi-interpenetrating network; MOF-808(Zr) nanoparticles are dispersed in the polyacrylamide-based hydrogel; the pore size of the MOF-808(Zr) nanoparticles is 0.29~0.3 nm; The thermosensitive copolymer contains gold nanorods; the local surface plasmon resonance peak of the gold nanorods is 798~818 nm.
[0017] In this invention, the particle size of the MOF-808(Zr) nanoparticles can be 50~200nm, specifically 100nm or 150nm; the specific surface area of the MOF-808(Zr) nanoparticles can be ≥1500m². 2 / g, which can be specifically 1550m 2 / g, 1600m 2 / g or 1650m 2 / g. This invention controls the particle size of MOF-808(Zr) nanoparticles within the range of 50~200nm, ensuring that the MOF-808(Zr) nanoparticles are not too small (<50nm) which would affect the sieving accuracy, and also avoids the MOF-808(Zr) nanoparticles being too large (>200nm) which would cause the particles to migrate into the formation pores and cause blockage.
[0018] In this invention, the pore size of the MOF-808(Zr) nanoparticles is 0.29~0.3 nm, specifically 0.292 nm, 0.295 nm, or 0.298 nm. The dynamic diameter of water molecules in the hydrogel is approximately 0.27~0.32 nm, which theoretically can enter the pores of the MOF-808(Zr) nanoparticles and may compete for adsorption sites, but still achieves effective hydrogen adsorption, indicating that under dynamic conditions, hydrogen preferentially occupies the pores compared to water molecules.
[0019] In this invention, the mass ratio of MOF-808(Zr) nanoparticles to polyacrylamide-based hydrogel can be 1~3:10, specifically 1.5:10, 2:10, or 2.5:10. By controlling the mass ratio of MOF-808(Zr) nanoparticles to polyacrylamide-based hydrogel to 1~3:10, this invention ensures the effective adsorption site density while avoiding excessive aggregation and clogging of the gel network by MOF-808(Zr) nanoparticles.
[0020] In this invention, the monomers of the thermosensitive copolymer may include a first acrylamide monomer and an acrylic monomer; the first acrylamide monomer may include one or more of N-isopropylacrylamide, N,N-diethylacrylamide, and N-tert-butylacrylamide; the acrylic monomer may include one or more of acrylic acid, methacrylic acid, ethylacrylic acid, crotonic acid, and 2-ethylacrylic acid. The molar ratio of the first acrylamide monomer to the acrylic monomer may be 6.7~9:1 (i.e., the molar percentage of the acrylic monomer in the monomers of the thermosensitive copolymer is 10~15 mol%), specifically 7:1, 8:1, or 8.5:1. In this invention, the critical dissolution temperature of the thermosensitive copolymer may be 43~47℃, specifically 44℃, 45℃, or 46℃. This invention controls the molar ratio of the first acrylamide monomer and the acrylic monomer to be 6.7~9:1, and adjusts the swelling rate of the composite gel core by ionization of carboxyl groups to ensure that the phase change shrinkage force is >5kPa. At the same time, it avoids excessive hydrophilicity caused by excessive use of acrylic monomers, which inhibits the hydrophobic locking function.
[0021] In this invention, the mass ratio of the polyacrylamide-based hydrogel to the thermosensitive copolymer can be 1:0.5~2, specifically 1:1 or 1:1.5. By controlling the mass ratio of the polyacrylamide-based hydrogel to the thermosensitive copolymer to 1:0.5~2, this invention ensures a balance between the mechanical stability of the interpenetrating network structure and its thermosensitive shrinkage properties, thus guaranteeing sufficient hydrogen adsorption capacity while achieving efficient and controllable release.
[0022] In this invention, the ratio of the total volume of the polyacrylamide-based hydrogel and the thermosensitive copolymer to the mass of the gold nanorods can be 1 mL: 0.5~2 mg, specifically 1 mL: 1 mg or 1 mL: 1.5 mg; the aspect ratio of the gold nanorods can be 3~5:1, specifically 3.5:1, 4:1 or 4.5:1; the local surface plasmon resonance peak of the gold nanorods is 798~818 nm, specifically 803 nm, 808 nm or 813 nm.
[0023] In this invention, the ratio of the thickness of the silicon carbide layer to the radius of the composite gel core can be 1:40~200, specifically 1:60, 1:100, or 1:150; the mass ratio of the silicon carbide layer to the composite gel core can be 1:5~20, specifically 1:10 or 1:15; the thickness of the silicon carbide layer can be 50~100 nm, specifically 60 nm, 75 nm, or 90 nm. This invention, by controlling the thickness of the silicon carbide layer to 50~100 nm, ensures the integrity of the coating to block H2S penetration while avoiding brittle cracking.
[0024] In this invention, a palladium catalyst may also be dispersed in the polyacrylamide-based hydrogel; the palladium catalyst comprises cerium dioxide and elemental palladium supported on the cerium dioxide. In this invention, the loading of elemental palladium on the cerium dioxide can be 1~5 wt%, specifically 2 wt%, 3 wt%, or 4 wt%; the cerium dioxide may have oxygen vacancy defects; the density of the oxygen vacancy defects can be ≥1.5 × 10⁻⁶. 20 cm -3 Specifically, it can be 1.6 × 10 20 cm -3 Or 1.8×10 20 cm -3 In this invention, the mass ratio of the palladium catalyst to the total mass of the polyacrylamide-based hydrogel and the thermosensitive copolymer can be 3:100. This invention, by dispersing a palladium catalyst in the core of the composite gel, oxidizes H2S in the formation to elemental sulfur, with the reaction formula 2H2S + O2 → 2S + 2H2O. This results in a composite hydrogel material with an H2S conversion rate >95% at 100℃, a sulfur capacity ≥60wt%, and a service life >5 years.
[0025] Figure 1 This is a schematic diagram of the structure of the composite hydrogel material provided by the present invention. The following is in conjunction with... Figure 1 The structure of the composite hydrogel material provided by this invention will be briefly described.
[0026] This invention provides a composite hydrogel material, comprising a composite gel core and a silicon carbide layer 3 coating the surface of the composite gel core; The composite gel core consists of a polyacrylamide-based hydrogel 1 and a thermosensitive copolymer 2 grafted onto the polyacrylamide-based hydrogel; the polyacrylamide-based hydrogel 1 and the thermosensitive copolymer 2 form an interpenetrating network or a semi-interpenetrating network; MOF-808 (Zr) nanoparticles 4 are dispersed in the polyacrylamide-based hydrogel 1. Gold nanorods 5 are dispersed in the thermosensitive copolymer 2; The polyacrylamide-based hydrogel 1 also contains a palladium catalyst 6.
[0027] In the composite hydrogel material provided by this invention, there is no obvious layering between the polyacrylamide-based hydrogel 1 and the thermosensitive copolymer 2 due to the formation of an interpenetrating network. However, since the preparation is carried out layer by layer, the gold nanorods 5 are still selectively distributed in the thermosensitive copolymer 2. The selective distribution of the gold nanorods is the key to realizing its function. The thermosensitive copolymer is precisely heated through the local surface plasmon resonance effect, triggering its phase transition shrinkage, thereby controlling the release of hydrogen. The MOF-808 (Zr) nanoparticles 4 and palladium catalyst 6 are selectively distributed in the polyacrylamide-based hydrogel 1. Although the MOF-808 (Zr) nanoparticles 4 and palladium catalyst 6 have physical contact with the thermosensitive copolymer 2, they are essentially still present in the polyacrylamide-based hydrogel 1.
[0028] This invention provides a method for preparing the composite hydrogel material described above, comprising the following steps: The second acrylamide monomer, crosslinking agent, initiator, MOF-808 (Zr) nanoparticles and water were mixed to obtain a mixed dispersion. The mixed dispersion is subjected to a crosslinking reaction in the oil phase, or the mixed dispersion is subjected to a crosslinking reaction in a spherical mold to obtain a spherical primary hydrogel; The spherical primary hydrogel, the polymer monomer of the thermosensitive copolymer, gold nanorods, and a polar aprotic solvent were mixed and subjected to a polymerization-grafting reaction to obtain a composite gel core. A silicon carbide layer is formed on the surface of the composite gel core to obtain a composite hydrogel material.
[0029] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.
[0030] This invention involves mixing a second acrylamide monomer, a crosslinking agent, an initiator, MOF-808 (Zr) nanoparticles, and water to obtain a mixed dispersion; In this invention, mixing the second acrylamide monomer, crosslinking agent, initiator, MOF-808 (Zr) nanoparticles and water may include the following steps: The second acrylamide monomer, crosslinking agent and water are mixed to obtain the first mixture; The first mixture was mixed with MOF-808(Zr) nanoparticles to remove oxygen, and then an initiator was added.
[0031] In this invention, the preparation method of the MOF-808(Zr) nanoparticles may include the following steps: ZrOCl2·8H2O, pyromellitic acid (H3BTC), acetic acid and an organic solvent were mixed and subjected to a solvothermal reaction to obtain the MOF-808(Zr) nanoparticles.
[0032] In this invention, the molar ratio of ZrOCl2·8H2O to trimesolic acid can be 1:0.8~1.2, specifically 1:0.9, 1:1, or 1:1.1; the organic solvent can be N,N-dimethylformamide; the mass ratio of ZrOCl2·8H2O to the organic solvent can be 1:20~60, specifically 1:30, 1:40, or 1:50; the volume ratio of acetic acid to the organic solvent can be 1:3~5, specifically 1:3.5, 1:4, or 1:4.5. In this invention, the temperature of the solvothermal reaction can be 80~120℃, specifically 90℃, 100℃, or 110℃; the time of the solvothermal reaction can be 12~36h, specifically 18h, 24h, or 30h.
[0033] After the solvothermal reaction is completed, the present invention may further include cooling the solvothermal reaction solution obtained from the solvothermal reaction and then separating the solid and liquid phases to obtain a solid phase; the solid phase is washed and dried to obtain the MOF-808(Zr) nanoparticles.
[0034] In this invention, the solid-liquid separation may include centrifugation; the washing may include washing with N,N-dimethylformamide and methanol. This invention removes unreacted substances by washing the resulting solid phase.
[0035] In this invention, the washing process can be repeated 2 to 3 times. Each washing cycle can specifically involve washing with N,N-dimethylformamide followed by washing with methanol. This invention uses methanol washing to replace residual N,N-dimethylformamide.
[0036] In this invention, the solid-liquid ratio of the solid phase to the N,N-dimethylformamide used in a single washing cycle can be 1g:10~20mL, specifically 1g:12mL, 1g:15mL or 1g:18mL.
[0037] In this invention, the drying process may include vacuum drying; the temperature of the vacuum drying may be 120°C. This invention uses vacuum drying to remove residual solvent from the pores of MOF-808(Zr) nanoparticles, thereby activating the MOF-808(Zr) nanoparticles.
[0038] In this invention, the second acrylamide monomer may include one or more of acrylamide, methacrylamide, and N-hydroxymethylacrylamide; the crosslinking agent may include one or more of N,N'-methylenebisacrylamide, p-divinylbenzene, N,N'-bis(acryloyl)cysteine, tetraallyloxyethane, ethylene glycol diacrylate, diacetone acrylamide, 3-acrylamidophenylboronic acid containing borate ester bonds, and terephthalaldehyde containing Schiff base bonds. Among the crosslinking agents used in this invention, p-divinylbenzene can improve gel strength; N,N'-bis(acryloyl)cysteine can achieve biodegradability; diacetone acrylamide can improve the tensile toughness of the hydrogel; 3-acrylamidophenylboronic acid containing borate ester bonds or terephthalaldehyde containing Schiff base bonds have dynamic covalent bonds that can reversibly break and recombine under mild conditions, thereby endowing the hydrogel with self-healing properties.
[0039] In this invention, the mass ratio of the second acrylamide monomer to the crosslinking agent can be 100:0.5~3, specifically 100:1, 100:2, or 100:2.5; the mass percentage of the second acrylamide monomer in the mixture formed by the second acrylamide monomer, crosslinking agent, initiator, MOF-808(Zr) nanoparticles, and water can be 8~12wt%, specifically 9wt%, 10wt%, or 11wt%. This invention, by controlling the mass ratio of the second acrylamide monomer to the crosslinking agent and the mass percentage of the second acrylamide monomer in the mixture, ensures that the gel network has suitable swelling rate and mechanical strength, thereby effectively fixing the MOF-808(Zr) nanoparticles and maintaining the stability of the composite structure.
[0040] In this invention, the initiator may include one or more of azo initiators, peroxide initiators, persulfate initiators, photoinitiators, and redox initiators; the mass ratio of the second acrylamide monomer to the initiator may be 100:0.5~1.5, specifically 100:0.8, 100:1, or 100:1.2.
[0041] In this invention, the azo initiator may include 2,2'-azobisisobutyramidine hydrochloride (AIBA). This invention uses a water-soluble azo initiator, which has high initiation efficiency, good water solubility and few residues, and is suitable for aqueous solution polymerization and emulsion polymerization.
[0042] In this invention, the peroxide initiator may include Fenton's reagent.
[0043] In this invention, the persulfate initiator may include one or more of potassium persulfate (KPS), ammonium persulfate (APS), and sodium persulfate (NaPS).
[0044] In this invention, the redox initiator may include an ammonium persulfate-sodium bisulfite (APS-NaHSO3) composite initiator, a potassium persulfate-sodium metabisulfite composite initiator, or an ammonium persulfate-sodium sulfite composite initiator.
[0045] In this invention, the photoinitiator may include Irgacure 2959.
[0046] After obtaining the mixed dispersion, the present invention performs a crosslinking reaction on the mixed dispersion in the oil phase, or performs a crosslinking reaction on the mixed dispersion in a spherical mold to obtain a spherical primary hydrogel.
[0047] In this invention, the temperature of the crosslinking reaction can be 60°C; the time of the crosslinking reaction can be 2 hours.
[0048] In this invention, the deoxygenation includes nitrogen deoxygenation; the nitrogen deoxygenation time can be 30 minutes.
[0049] In this invention, the oil phase may include paraffin oil; the temperature of the oil phase may be the same as the temperature of the crosslinking reaction, which will not be elaborated further here. In this invention, the oil phase may also include a nonionic surfactant, specifically sorbitan monooleate (Span 80); the mass percentage of the nonionic surfactant in the oil phase may specifically be 1%.
[0050] In this invention, the crosslinking reaction in the oil phase may include the following steps: dropping the mixed dispersion into the oil phase to carry out the crosslinking reaction. This invention prepares spherical primary hydrogels via a drop-in method. By dropping the mixed liquid into an incompatible oil phase medium, the dropped liquid naturally forms spherical shapes under the action of surface tension, completes the crosslinking reaction, and solidifies to form a spherical primary hydrogel.
[0051] In this invention, the crosslinking reaction in the spherical mold may include the following steps: injecting the mixed dispersion into the spherical mold for the crosslinking reaction, followed by demolding. This invention prepares spherical primary hydrogels using a template method, allowing the mixed dispersion to naturally solidify along the mold shape within the mold to form a spherical shape, thus enabling precise control over the size and shape of the spherical primary hydrogel.
[0052] After obtaining the spherical primary hydrogel, the present invention mixes the spherical primary hydrogel, the polymerizable monomer of the thermosensitive copolymer, gold nanorods and a polar aprotic solvent to carry out a polymerization-grafting reaction to obtain a composite gel core.
[0053] In this invention, mixing the spherical primary hydrogel, the polymer monomer of the thermosensitive copolymer, the gold nanorods, and the polar aprotic solvent may include the following steps: The polymer monomers of the thermosensitive copolymer are mixed with a polar aprotic solvent to obtain a second mixture; The spherical primary hydrogel was immersed in the second mixture, and then gold nanorods were added and mixed.
[0054] In this invention, the polar aprotic solvent may include water, ethanol, methanol, isopropanol, dimethyl sulfoxide, and N,N-dimethylformamide; when the polar aprotic solvent includes water and ethanol, the volume ratio of water to ethanol may be 1:1.
[0055] In this invention, the temperature of the polymerization-grafting reaction can be 25°C; the time of the polymerization-grafting reaction can be 1 to 4 hours, specifically 2 hours or 3 hours; the polymerization-grafting reaction can be carried out in a nitrogen atmosphere.
[0056] After obtaining the composite gel core, the present invention forms a silicon carbide layer on the surface of the composite gel core to obtain a composite hydrogel material.
[0057] In this invention, forming the silicon carbide layer may include the following steps: The precursor is subjected to plasma-enhanced chemical vapor deposition on the surface of the composite gel core to form a silicon carbide layer on the surface of the composite gel core.
[0058] In this invention, the precursor includes one or more of trimethylsilane, tetramethylsilane, hexamethyldisilane, methyltrichlorosilane, and monosilane-methane mixtures. In this invention, the plasma atmosphere for plasma-enhanced chemical vapor deposition can be an argon plasma atmosphere; the temperature for plasma-enhanced chemical vapor deposition can be 250~400℃, specifically 300℃ or 350℃.
[0059] In this invention, when a palladium catalyst is also dispersed in the composite gel core, the preparation method of the composite hydrogel material may include the following steps: The second acrylamide monomer, crosslinking agent, initiator, MOF-808 (Zr) nanoparticles, palladium catalyst and water were mixed and crosslinked in the oil phase to obtain a spherical primary hydrogel. The spherical primary hydrogel, the polymer monomer of the thermosensitive copolymer, gold nanorods, and a polar aprotic solvent were mixed and subjected to a polymerization-grafting reaction to obtain a composite gel core. A silicon carbide layer is formed on the surface of the composite gel core to obtain a composite hydrogel material.
[0060] In this invention, the method for preparing the palladium catalyst may include the following steps: Cerium nitrate hexahydrate, sodium hydroxide and water were mixed and aged to precipitate. The precipitate was washed, dried and then calcined in air to decompose it, thus obtaining a cerium dioxide carrier with oxygen vacancy defects. Palladium chloride, water, and hydrochloric acid were mixed to obtain a palladium precursor solution; The cerium dioxide support was dispersed in deionized water, and the palladium precursor solution was added to the resulting dispersion. The pH of the system was adjusted to 8.5-9.5 with sodium carbonate solution, and the mixture was stirred and impregnated at room temperature to obtain a suspension. Hydrogen gas is introduced into the suspension for reduction treatment, reducing the palladium precursor to elemental palladium, which is then loaded onto the surface of a cerium dioxide support to obtain a reduction product. The obtained reduction product is centrifuged, washed repeatedly with deionized water and ethanol, and dried under vacuum to obtain the palladium catalyst.
[0061] In this invention, the molar ratio of cerium nitrate hexahydrate to sodium hydroxide can be 1:4; the calcination temperature can be 500℃; the calcination time can be 4h; the concentration of the sodium carbonate solution can be 0.1mol / L; the stirring and impregnation time can be 6h; the reduction treatment temperature can be 25℃; the reduction treatment time can be 2h; the hydrogen flow rate can be 50mL / min; the vacuum drying temperature can be 60℃; and the vacuum drying time can be 12h.
[0062] In this invention, the preparation method of the composite hydrogel material is the same as described above, and will not be repeated here. This invention physically embeds the palladium catalyst within the three-dimensional network of the polyacrylamide-based hydrogel by directly adding the palladium catalyst to the mixed system and then carrying out a crosslinking reaction. Since the palladium catalyst particle size is similar to that of MOF particles (50~200 nm), and the reaction system remains homogeneously dispersed before gelation, uniform immobilization throughout the polyacrylamide-based hydrogel can be achieved through in-situ polymerization.
[0063] This invention provides the application of the composite hydrogel material described in the above technical solution or the composite hydrogel material prepared by the above technical solution in the adsorption, storage and controlled release of hydrogen.
[0064] This invention provides a hydrogen adsorption-storage-release system, comprising a hydrogen adsorption material and a near-infrared light source; The hydrogen adsorption material is the composite hydrogel material described in the above technical solution or the composite hydrogel material prepared by the preparation method described in the above technical solution.
[0065] In this invention, the system may further include a hydrogen extraction component; the hydrogen extraction component may include a screen tube. This invention uses the screen tube to collect the released hydrogen and return it to the production well for recovery.
[0066] In this invention, the near-infrared light source may include a near-infrared laser emitting device; the output wavelength of the near-infrared laser emitting device may be 798~818nm, specifically 803nm, 808nm, or 813nm; the output power density of the near-infrared laser emitting device may be 1~5W / cm². 2 Specifically, it can be expressed as 2W / cm 2 3W / cm 2 Or 4W / cm 2 The near-infrared laser emitting device can guide near-infrared laser light down into the well via armored optical fiber.
[0067] This invention provides a method for hydrogen adsorption-storage-release using the system described above, wherein the adsorption and storage include: injecting a solution containing hydrogen adsorption material into an aqueous hydrogen storage layer, so that the hydrogen adsorption material adsorbs hydrogen in the aqueous hydrogen storage layer to obtain a closed hydrogen storage unit. The release includes: irradiating the sealed hydrogen storage unit with a near-infrared light source to cause the sealed hydrogen storage unit to release hydrogen gas.
[0068] In this invention, the solid content of the solution containing the hydrogen adsorbent material can be 8 wt%; the solvent of the solution containing the hydrogen adsorbent material can be an ethanol-water mixture, dimethyl sulfoxide, or N,N-dimethylformamide. In one embodiment of this invention, the volume ratio of ethanol to water in the ethanol-water mixture can specifically be 1:1.
[0069] Figure 2 The present invention provides a flowchart of a hydrogen adsorption-storage-release method; Figure 3 A schematic diagram of the in-situ adsorption and permeation diffusion mechanism of hydrogen in underground reservoirs; Figure 4 This is a schematic diagram of the adsorption and storage principle of composite hydrogel materials (where (a) is the state of the composite hydrogel material swelling to form a porous adsorption structure, (b) is the selective adsorption of hydrogen molecules through the pores of MOF-808(Zr) to a saturated state, and (c) is the state of the thermosensitive polymer hydrophobic shrinkage locking hydrogen to form a closed hydrogen storage unit). Figure 5 This is a schematic diagram of the kinetic quantum sieving effect process of MOF-808(Zr) nanoparticles (where (a) shows the state of H2 and CH4 approaching the pores of MOF-808(Zr), (b) shows the kinetic quantum sieving process, and (c) shows the selective adsorption of H2 into the pores and the achievement of a saturated locked state). Figure 6 A schematic diagram illustrating the principle of releasing hydrogen from a closed hydrogen storage unit; Figure 7 This is a schematic diagram illustrating the corrosion resistance principle of composite hydrogel materials. The following section combines... Figures 2-7 The present invention provides a detailed description of the hydrogen adsorption-storage-release method and the corrosion-resistant working mechanism of the composite hydrogel material.
[0070] In this invention, a solution containing hydrogen adsorbent material is injected into the underground reservoir 29 through injection well 7, and diffuses into the pores of the underground reservoir 29 along the direction of the concentration 12 of the solution containing hydrogen adsorbent material (the spatial gradient distribution in which the concentration of the solution containing hydrogen adsorbent material gradually decreases with increasing diffusion distance as it permeates and diffuses outward from the injection well in the formation pores, i.e., the farther away from the injection well, the lower the solution concentration). Upon encountering formation water 13, it swells to form swollen microspheres 9. The mixed gas (containing H2 molecules 10, CH4 molecules 14, and H2S molecules 18) in the underground reservoir 29 diffuses into the swollen microspheres 9. The H2 molecule 10 has a diameter 21 (kinetic diameter) of 0.289 nm, which is smaller than the diameter of the MOF-808(Zr) channel 19 (0.29 nm, i.e., the MOF-808(Zr) pore size 20), allowing it to enter the MOF-808(Zr) pores and be selectively adsorbed. The CH4 molecule 14 has a diameter 22 of 0.38 nm, which is larger than the MOF-808(Zr) pore size 20, and is blocked by the kinetic quantum sieving effect. Simultaneously, the formation water 13 swells into the microspheres 9, forming a porous structure 15, which promotes the diffusion of H2 molecules 10 along the hydrogen migration and diffusion concentration 11 direction. Figure 3 China and Figure 4 (in the direction of the red arrow in (c)) enrichment towards MOF-808(Zr)4. Upon adsorption saturation, the hydrophobic group 16 in the thermosensitive copolymer 2 triggers hydrophobic shrinkage of the gel along the hydrogel shrinkage region 17, reducing the hydrogen diffusion coefficient to 5 × 10⁻⁶. -13 m 2 The H2 molecules are locked within the swollen microspheres 9 at a rate of / s; although the H2S molecules 18 come into contact with the surface of the swollen microspheres 9, they are blocked from corrosion by the silicon carbide layer 3.
[0071] When the adsorbed hydrogen needs to be released, the gold nanorods 5 are irradiated by the near-infrared light source 23 (downhole near-infrared laser). The thermal radiation 24 causes the polymer chains to contract, resulting in a volume phase transition of the composite hydrogel material along the volume phase transition contraction region 25, and the H2 molecules 10 are rapidly released. At the same time, the palladium catalyst 6 immobilized in the core of the composite gel comes into contact with the H2S molecules 18 and catalytically oxidizes them to elemental S 26 and the reaction product water molecules 27 in the presence of oxygen, achieving self-purification and forming a catalytic oxidation anti-corrosion region 28 to prevent the palladium catalyst 6 from being poisoned.
[0072] To further illustrate the present invention, the solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0073] In all embodiments of the present invention, acrylamide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. or McLean Company; crosslinking agent N,N'-methylenebisacrylamide was purchased from Aladdin or McLean; initiator ammonium persulfate was purchased from Aladdin; thermosensitive copolymer monomer N-isopropylacrylamide was purchased from Aladdin or Sigma-Aldrich; acrylic acid was purchased from Aladdin or McLean; gold nanorods were purchased from Nanjing Dongna Biotechnology Co., Ltd. or Beijing Zhongke Keyou Technology Co., Ltd.; and silicon carbide layer precursor trimethylsilane was purchased from Baoding Northern Special Gases Co., Ltd. (electronic grade).
[0074] The palladium catalyst was prepared by dissolving cerium nitrate hexahydrate in deionized water, adding sodium hydroxide solution, stirring and aging at room temperature, washing and drying the resulting precipitate with deionized water, and then calcining it at 500℃ in air for 4 hours to obtain an oxygen vacancy defect density ≥1.5×10⁻⁶. 20 cm -3 A cerium dioxide support was prepared, wherein the molar ratio of cerium nitrate hexahydrate to sodium hydroxide was 1:4. The amount of palladium chloride used was calculated based on a Pd loading of 3 wt% in the obtained palladium catalyst. Palladium chloride was dissolved in deionized water, and dilute hydrochloric acid was added to aid dissolution. The mixture was stirred until completely dissolved to obtain a palladium precursor solution. The obtained cerium dioxide support was dispersed in deionized water and ultrasonically dispersed until uniform. The obtained palladium precursor solution was then slowly added dropwise, while the pH of the system was adjusted to 9 using a 0.1 mol / L sodium carbonate solution. The mixture was stirred and impregnated at room temperature for 6 hours to obtain a suspension. Hydrogen gas was introduced into the obtained suspension, and a reduction treatment was performed at 25 °C for 2 hours at a hydrogen flow rate of 50 mL / min to reduce the palladium precursor to elemental palladium, which was then loaded onto the surface of the cerium dioxide support. After reduction, the obtained reduction product was centrifuged, washed repeatedly with deionized water and ethanol, and vacuum dried at 60 °C for 12 hours to obtain the palladium catalyst.
[0075] Example 1 ZrOCl2·8H2O and trimesic acid were dissolved in N,N-dimethylformamide, and then acetic acid was added. After dissolving by stirring at room temperature, the solution was transferred to a high-pressure reactor and subjected to a solvothermal reaction at 100℃ for 24 h. After the reaction was completed, the resulting solvothermal reaction solution was cooled and centrifuged. The obtained solid phase was washed multiple times with N,N-dimethylformamide and methanol to remove unreacted substances, and then activated by vacuum drying at 120℃ to obtain MOF-808(Zr) nanoparticles with a particle size of 100 nm, a pore size of 0.29 nm, and a BET specific surface area ≥1500 m². 2 / g. The molar ratio of ZrOCl2·8H2O to trimesolic acid is 1:1, the mass ratio of ZrOCl2·8H2O to N,N-dimethylformamide is 1:20, and the volume ratio of acetic acid to N,N-dimethylformamide is 1:4.
[0076] Acrylamide and N,N'-methylenebisacrylamide were dissolved in deionized water to obtain a first mixture, wherein the mass ratio of acrylamide to N,N'-methylenebisacrylamide was 100:1.5 and the mass ratio of acrylamide to deionized water was 1:5.
[0077] MOF-808(Zr) nanoparticles were added to the obtained first mixture. After purging with nitrogen for 30 min to remove oxygen, ammonium persulfate was added. The resulting mixed dispersion was then dripped uniformly through a syringe needle into hot paraffin oil (containing 1% Span 80 by mass) at 60°C. The droplets of the mixed dispersion naturally formed spherical shapes under the action of surface tension. The mixture was then subjected to a cross-linking reaction at 60°C for 2 h to solidify. The resulting solid was removed and repeatedly washed with deionized water and ethanol to remove the hot paraffin oil, yielding a spherical primary hydrogel. The mass ratio of MOF-808(Zr) nanoparticles to polyacrylamide-based hydrogel in the spherical primary hydrogel was 2:10, and the mass ratio of ammonium persulfate to acrylamide was 1:200.
[0078] N-Isopropylacrylamide and acrylic acid were dissolved in deionized water at a molar ratio of 10:1 to obtain a second mixture, wherein the mass ratio of N-isopropylacrylamide to deionized water was 1:10.
[0079] The obtained spherical primary hydrogel was immersed in a second mixture, and gold nanorods with an aspect ratio of 4:1 were added. A polymerization-grafting reaction was carried out at 25°C for 2 hours to obtain a composite gel core. The core structure consisted of a polyacrylamide-based hydrogel and a thermosensitive copolymer grafted onto the polyacrylamide-based hydrogel. The polyacrylamide-based hydrogel and the thermosensitive copolymer formed an interpenetrating network or a semi-interpenetrating network. MOF-808 (Zr) nanoparticles were dispersed in the polyacrylamide-based hydrogel, and gold nanorods were dispersed in the thermosensitive copolymer. The total volume ratio of the polyacrylamide-based hydrogel and the thermosensitive copolymer to the mass ratio of the gold nanorods was 1 mL:1 mg.
[0080] Using trimethylsilane as a precursor, a silicon carbide layer with a thickness of 80 nm was formed on the surface of the core of the obtained composite gel by plasma-enhanced chemical vapor deposition under an argon plasma atmosphere and a temperature of 300 °C, thus obtaining a composite hydrogel material.
[0081] The method for hydrogen adsorption-storage-release using composite hydrogel materials is as follows: Hydrogen adsorption and storage: A solution containing hydrogen adsorbent material with a solid content of 8 wt% (i.e., a mass ratio of 8:92 between the composite hydrogel material and the ethanol-water mixture) was prepared by mixing a composite hydrogel material and an ethanol-water mixture. The volume ratio of ethanol to water in the ethanol-water mixture was 1:1. The solution containing the hydrogen adsorbent material was injected into an aqueous hydrogen storage layer. Upon contact with formation water, the composite hydrogel material swelled to form microspheres with a diameter of 3-5 mm, achieving a swelling rate of 1200% and a specific surface area from 600 m² / m³. 2 / g increased to 850m 2 / g, achieving in-situ adsorption of hydrogen, with an adsorption saturation and a hydrogen diffusion coefficient of 5×10. -13 m 2 A closed hydrogen storage unit with a capacity of / s.
[0082] Hydrogen release: An output wavelength of 808nm and a power density adjustable range of 1~5W / cm² are used. 2 The near-infrared laser emitting device transmits a power density of 2W / cm² into the well via armored optical fiber. 2 The 808nm near-infrared laser causes the gel in the sealed hydrogen storage unit to complete a volume phase transition and shrink within 50 seconds, releasing 93.5% of the hydrogen in 5 minutes. The released hydrogen is then collected through the screen tube and recycled to the production well.
[0083] Example 2 The composite hydrogel material was prepared using the method provided in Example 1. The only difference from Example 1 is that, in the stage of preparing the spherical primary hydrogel, acrylamide, crosslinking agent, initiator, MOF-808 (Zr) nanoparticles, and palladium catalyst were added to water and mixed to obtain a mixed dispersion. The obtained mixed dispersion was dripped uniformly into hot paraffin oil (containing 1% Span 80 by mass) at 60°C through a syringe needle. The droplets of the mixed dispersion naturally formed spherical shapes under the action of surface tension. The crosslinking reaction was carried out at 60°C for 2 hours to solidify. The obtained solid was removed and repeatedly washed with deionized water and ethanol to remove the hot paraffin oil, thus obtaining the spherical primary hydrogel. The palladium catalyst consisted of CeO2 and elemental Pd supported on CeO2, with a Pd loading of 3 wt% and an oxygen vacancy density of 1.8 × 10⁻⁶. 20 cm -3 The mass ratio of the palladium catalyst to the total mass of the polyacrylamide-based hydrogel and the thermosensitive copolymer is 3:100.
[0084] Test Example 1 The corrosion resistance, photothermal release effect, and long-term stability of the composite hydrogel material prepared in Example 2 were tested. Gas chromatography (GC) was used to determine the gas composition, thermogravimetric analysis (TGA) to determine the sulfur capacity, and scanning electron microscopy (SEM) to observe the corrosion morphology. The test methods and results are as follows: Corrosion resistance: The composite hydrogel material was placed in a mixed gas environment containing 500 ppm H2S and 5% O2 at 100℃, with continuous steam injection to activate the reaction. Results showed that the H2S conversion rate reached 96.7%, and the palladium catalyst activity in the composite hydrogel material remained at 95% of its initial value even when the sulfur capacity accumulated to 63 wt%. Accelerated aging tests indicated that after 1800 hours of operation at 150℃, the corrosion rate of the composite hydrogel material was only 0.007 mm / year, meeting the 5-year service life requirement.
[0085] Photothermal release effect: An artificial sandstone reservoir model with a diameter of 10 cm and a length of 50 cm was constructed, with a porosity of 15% and a permeability of 8 mD. After injecting a solution containing hydrogen adsorbent material, a mixed gas containing 4% H2 and 200 ppm H2S was introduced. After adsorption saturation, two release schemes were compared: the experimental group used an 808 nm near-infrared laser (power density 2 W / cm²). 2 The experimental group was triggered to release hydrogen; the control group was heated to 50°C using conventional electric heating. The results showed that the experimental group recovered 91.2% of hydrogen within 4 minutes and 30 seconds, with an energy consumption of 0.8 kWh / kg H2; the control group required heating for 35 minutes, with an energy consumption of 4.2 kWh / kg H2, and the H2 recovery rate was only 78.5%.
[0086] Long-term stability: The composite hydrogel material was subjected to 50 "adsorption-storage-release" cycles under conditions of 90℃, 10MPa, and 300ppm H2S concentration. Each cycle lasted 72 hours for adsorption, and release was triggered by an 808nm near-infrared laser. Results showed that after 50 cycles, the H2 adsorption capacity of the composite hydrogel material decreased by less than 5%, the photothermal response time increased to 7 seconds, the H2S conversion rate remained at 94.3%, and no visible corrosion pits were observed in the silicon carbide layer. Based on the Arrhenius equation, the composite hydrogel material, at this decay rate, has a service life exceeding 5.8 years in sulfur-containing formations at 80℃.
[0087] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A composite hydrogel material, characterized in that, It includes a composite gel core and a silicon carbide layer covering the surface of the composite gel core; The composite gel core consists of a polyacrylamide-based hydrogel and a thermosensitive copolymer grafted onto the polyacrylamide-based hydrogel; the polyacrylamide-based hydrogel and the thermosensitive copolymer form an interpenetrating network or a semi-interpenetrating network; MOF-808(Zr) nanoparticles are dispersed in the polyacrylamide-based hydrogel; the pore size of the MOF-808(Zr) nanoparticles is 0.29~0.3 nm; The thermosensitive copolymer contains gold nanorods; the local surface plasmon resonance peak of the gold nanorods is 798~818 nm.
2. The composite hydrogel material according to claim 1, characterized in that, The MOF-808(Zr) nanoparticles have a particle size of 50~200nm; the mass ratio of the MOF-808(Zr) nanoparticles to the polyacrylamide-based hydrogel is 1~3:
10.
3. The composite hydrogel material according to claim 1, characterized in that, The mass ratio of the polyacrylamide-based hydrogel to the thermosensitive copolymer is 1:0.5~2; The critical dissolution temperature of the thermosensitive copolymer is 43~47℃; The polymer monomers of the thermosensitive copolymer include a first acrylamide monomer and an acrylic monomer; The first acrylamide monomer includes one or more of N-isopropylacrylamide, N,N-diethylacrylamide and N-tert-butylacrylamide; The acrylic monomers include one or more of acrylic acid, methacrylic acid, ethylacrylic acid, butenoic acid, and 2-ethylacrylic acid; The molar ratio of the first acrylamide monomer to the acrylic monomer is 6.7~9:1; The ratio of the total volume of the polyacrylamide-based hydrogel and the thermosensitive copolymer to the mass of the gold nanorods is 1 mL: 0.5~2 mg; The aspect ratio of the gold nanorods is 3~5:
1.
4. The composite hydrogel material according to claim 1, characterized in that, The polyacrylamide-based hydrogel also contains a palladium catalyst. The palladium catalyst comprises cerium dioxide and elemental palladium supported on the cerium dioxide.
5. The method for preparing the composite hydrogel material according to any one of claims 1 to 4, characterized in that, Includes the following steps: The second acrylamide monomer, crosslinking agent, initiator, MOF-808 (Zr) nanoparticles and water were mixed to obtain a mixed dispersion. The mixed dispersion is subjected to a crosslinking reaction in the oil phase, or the mixed dispersion is subjected to a crosslinking reaction in a spherical mold to obtain a spherical primary hydrogel; The spherical primary hydrogel, the polymer monomer of the thermosensitive copolymer, gold nanorods, and a polar aprotic solvent were mixed and subjected to a polymerization-grafting reaction to obtain a composite gel core. A silicon carbide layer is formed on the surface of the composite gel core to obtain a composite hydrogel material.
6. The preparation method according to claim 5, characterized in that, The second type of acrylamide monomer includes one or more of acrylamide, methacrylamide, and N-hydroxymethylacrylamide; The crosslinking agent includes one or more of N,N'-methylenebisacrylamide, p-divinylbenzene, N,N'-bis(acryloyl)cysteine, tetraenylpropoxyethane, ethylene glycol diacrylate, and diacetone acrylamide; The initiator includes one or more of azo initiators, peroxide initiators, persulfate initiators, photoinitiators, and redox initiators; The mass ratio of the second acrylamide monomer to the crosslinking agent is 100:0.5~3; The mass ratio of the second acrylamide monomer to the initiator is 100:0.5~1.5; The crosslinking reaction was carried out at a temperature of 60°C for 2 hours. The polymerization-grafting reaction is carried out at a temperature of 25°C for 1 to 4 hours.
7. The preparation method according to claim 5, characterized in that, When the composite hydrogel core also contains a palladium catalyst, the preparation method of the composite hydrogel material includes the following steps: The second acrylamide monomer, crosslinking agent, initiator, MOF-808 (Zr) nanoparticles, palladium catalyst and water were mixed to obtain a mixed dispersion. The mixed dispersion is subjected to a crosslinking reaction in the oil phase, or the mixed dispersion is subjected to a crosslinking reaction in a spherical mold to obtain a spherical primary hydrogel; The spherical primary hydrogel, the polymer monomer of the thermosensitive copolymer, gold nanorods, and a polar aprotic solvent were mixed and subjected to a polymerization-grafting reaction to obtain a composite gel core. A silicon carbide layer is formed on the surface of the composite gel core to obtain a composite hydrogel material.
8. The application of the composite hydrogel material according to any one of claims 1 to 4 or the composite hydrogel material prepared by the preparation method according to any one of claims 5 to 7 in the adsorption, storage and controlled release of hydrogen.
9. A hydrogen adsorption-storage-release system, comprising a hydrogen adsorption material and a near-infrared light source; The hydrogen adsorption material is the composite hydrogel material according to any one of claims 1 to 4 or the composite hydrogel material prepared by the preparation method according to any one of claims 5 to 7.
10. A method for hydrogen adsorption-storage-release using the system of claim 9, characterized in that, The adsorption and storage include: injecting a solution of hydrogen-containing adsorption material into an aqueous hydrogen storage layer, so that the hydrogen adsorption material adsorbs hydrogen in the aqueous hydrogen storage layer to obtain a closed hydrogen storage unit. The release includes: irradiating the sealed hydrogen storage unit with a near-infrared light source to cause the sealed hydrogen storage unit to release hydrogen gas.